'I gave that cue.' Integrating dance studies, praxeology, and computational perspectives to model change in the case study of William Forsythe's Duo. Issue 1 (2nd January 2021) - Waterhouse, Elizabeth; Jenett, Florian; Hager, Monika; Coniglio, Mark
ABSTRACT: Choreographer William Forsythe calls the work Duo a 'project'—reflecting the piece's long history of vicissitudes from 1996 to the present. We attempt to visualize continuity and change over several iterations of Duo, spanning a period of 20 years. Our methods involved graphical and statistical approaches to performance video annotation, considering seven videos acquired from Forsythe's private archive. Collaboration with Duo dancers was critical to develop this choreographic knowledge. The duet Duo was chosen to focus on annotation of partnering, choreographic structure, and interpretation; the case study furthermore enabled review of annotation methods from Forsythe's Synchronous Objects for One Flat Thing, reproduced (Forsythe et al. 2009) and built upon prior research of entrainment in Duo (Waterhouse, Watts, and Bläsing 2014). Studying a choreography longitudinally, with close regard of the performers' testimonies and digital traces, the problem required innovative methods. For this article, we focus on how annotation was used within this project. We outline our particular interdisciplinary approach, merging perspectives from dance studies, praxeology and creative coding. We present the language and concepts of annotation chosen, technical tools used for annotating, procedures of annotation analysis, and conclusions of the research. Thereby we present novel visualizations of choreographic process.